Low-level laser therapy as an antimicrobial and antibiofilm technology and its relevance to wound healing. (February 2015) - Percival, Steven L; Francolini, Iolanda; Donelli, Gianfranco
ABSTRACT : The biostimulative effect of low-level laser therapy (LLLT) in tissues has been noted in reference to the treatment of various diseases but little information exists on its effectiveness on chronic wounds and biofilm. The scope of this review was to identify literature reporting on LLLT alone, without photodynamic agents, as an antimicrobial/antibiofilm technology and determine its effects on wound healing. Overall the beneficial effects of LLLT in promoting wound healing in animal and human studies has been demonstrated. However, the lack of credible studies using reproducible models and light dosimetry restricts the analysis of current data. Efforts must be addressed to standardize phototherapy procedures as well as to develop suitable in vitro and in vivo biofilm models to test LLLT efficacy in promoting biofilm eradication and wound healing.